Intraoral scanner featuring transillumination for proximal caries detection. An in vitro validation study on permanent posterior teeth. (January 2022) - Michou, Stavroula; Vannahme, Christoph; Bakhshandeh, Azam; Ekstrand, Kim R.; Benetti, Ana R.
Abstract: Objectives: To assess the validity of an intraoral scanner system featuring near-infrared (NIR) transillumination to aid the detection of proximal caries lesions, and to compare the diagnostic performance of this system with that of conventional caries detection methods and with that of an intraoral camera featuring NIR transillumination (DIAGNOcam). Methods: Ninety-five permanent posterior teeth were examined using a prototype tip functioning with TRIOS 4 intraoral scanner system (3Shape TRIOS A/S, Denmark) and emitting NIR light, DIAGNOcam, and visual and radiographic examination employing ICDAS criteria. One or two approximal surfaces per tooth, sound or with caries lesions at different stages, were examined ( N1 =158). Histological assessment was used as the reference standard. Results: All methods showed excellent intra-examiner reliability ( κintra ≥0.80). Two independent examiners assessed the NIR images obtained with both devices. The first examiner, who obtained and assessed the images, showed improved diagnostic performance than the second examiner, who only had access to the images. The inter-examiner agreement between the two examiners assessing the NIR images was substantial ( κinter 0.57-0.72). The intraoral scanner and DIAGNOcam showed similar diagnostic performance. Regarding initial caries lesions, the NIR image assessment resulted in equal or improved sensitivity (SE 0.50-0.89) compared to radiographic assessment (SE 0.49-0.51) and higher than visual examination (SE 0.28-0.39). Radiographic and NIR image assessment resulted in similar SE in detecting moderate-extensive dentin caries lesions (SE 0.59-0.70), while visual examination showed an inferior value (SE 0.30). Conclusions: The intraoral scanner system featuring NIR transillumination and DIAGNOcam showed an overall good diagnostic performance. The conventional caries detection methods showed inferior sensitivity at initial caries lesion stages. Clinical significance: Considering the promising diagnostic performance of the intraoral scanner featuring transillumination and the advantages offered by combining the NIR images with the 3D models of the teeth, this system has the potential to contribute towards more reliable caries detection and monitoring in clinical practice without the use of ionizing radiation.